DIGITALISASI UMKM DALAM PROGRAM PERGURUAN TINGGI MANDIRI GOTONG ROYONG MEMBANGUN DESA (PTMGRMD) LLDIKTI IV JAWA BARAT DAN BANTEN - Lusiana, Irma Astri; Muanifah, Suciati; Wildan, M.; Ginting, Fajar Mediawan (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The digitalization of Micro, Small, and Medium Enterprises (MSMEs) has become a crucial strategy in the era of globalization and technological advancement. This service program aimed to support the digital transformation of MSMEs in Desa Cipicung, Kabupaten Pandeglang, enhancing their market competitiveness and empowering local businesses. The activities included workshops, hands-on training, and mentoring sessions tailored to the specific needs of MSMEs. The results indicated significant improvements in digital marketing skills, branding, and market reach. Participants successfully created online storefronts, utilized social media for promotions, and collaborated with local cooperatives to strengthen distribution networks. Despite challenges such as limited internet access and low digital literacy, the program demonstrated that digital tools could empower MSMEs to thrive in a competitive digital economy. This initiative serves as a replicable model for other rural areas to foster economic growth through digitalization. The purpose of this service was to support the digitalization of MSMEs in Desa Cipicung to enhance their competitiveness in the digital economy. The activities involved workshops, hands-on training, and mentoring sessions tailored to the specific needs of local MSMEs. Local MSMEs gained practical knowledge of digital marketing strategies, established online storefronts, and improved their product branding and market reach. The digitalization program successfully empowered MSMEs to adopt digital tools, thereby increasing their market competitiveness